Restorasi Sebagai Pertanggungjawaban Pemulihan Fungsi Lingkungan Hidup Bagi Perusahaan Pemegang Izin Usaha Pertambangan - Lingga Parama Liofa; Dewanto, Wisnu Aryo (Fakultas Hukum Universitas Surabaya, 2023)
Mining is a business that operates in the exploitation of natural resources, so the potential for natural damage is something that must be faced and addressed wisely. The Law on Environmental Protection and Management has made it mandatory for every person who pollutes the environment to restore environmental functions, one of which is restoration. In summary, restoration is an effort to restore environmental functions in the form of restoring the environment to its original condition. However, the Law on Mineral and Coal Mining stipulates that if the IUP or IUPK holder uses mining services, the responsibility for mining business activities remains borne by the IUP or IUPK holder. This results in a conflict of laws, resulting in a legal vacuum that requires mining service providers to carry out restoration as an action to restore environmental functions. Based on this, this research aims to analyze whether mining service providers whose services are used by mineral and coal mining can be required to carry out restoration as a form of responsibility for restoring environmental functions. The results of this research show that the imposition of mining responsibilities on IUP or IUPK holders also has an impact on the absence of obligations on mining service providers to carry out restoration.